2019
DOI: 10.3758/s13414-019-01669-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of eye movements in manual responses to social and nonsocial cues

Abstract: Gaze and arrow cues cause covert attention shifts even when they are uninformative. Nonetheless, it is unclear to what extent oculomotor behavior influences manual responses to social and nonsocial stimuli. In two experiments, we tracked the gaze of participants during the cueing task with nonpredictive gaze and arrow cues. In Experiment 1, the discrimination task was easy and eye movements were not necessary, whereas in Experiment 2 they were instrumental in identifying the target. Validity effects on manual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 62 publications
1
18
5
Order By: Relevance
“…Our findings from Experiments 1 and 2 contrast with those of Xu and Tanaka (2015) and Bonmassar et al (2019) who found that the magnitude of the cuing effect for both gaze and arrow cues was larger when the task was more difficult due to either added distracters or greater target task demands, respectively. Instead, our findings support those of Friesen et al (2005).…”
Section: Experiments 3-discrimination Task With Low Versus High Distracontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings from Experiments 1 and 2 contrast with those of Xu and Tanaka (2015) and Bonmassar et al (2019) who found that the magnitude of the cuing effect for both gaze and arrow cues was larger when the task was more difficult due to either added distracters or greater target task demands, respectively. Instead, our findings support those of Friesen et al (2005).…”
Section: Experiments 3-discrimination Task With Low Versus High Distracontrasting
confidence: 99%
“…This difference between the effects on attention from gaze and arrow cues is unusual and to our knowledge is the first demonstration of significantly weaker orienting in response to gaze versus arrow cues. Neither Bonmassar et al (2019) nor Xu and Tanaka (2015) found a difference in cuing magnitude between gaze and arrow cues in their bilateral distracter conditions, so it is not simply the removal of sudden target onset (by presenting information on the other side of the cue) that could account for our finding. For Experiment 2, it is notable that there is no significant facilitatory influence of the gaze cue at the 500 ms SOA and the 750 ms SOA, yet there is at the 150, 300, and 1,000 ms SOAs.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This result adds to the growing body of evidence demonstrating dissociations between covert and overt measures of social attention, in that the two modes of orienting appear to serve different purposes in real-world social environments—covert attention is hypothesized to serve as a mechanism that surreptitiously gathers information from the environment, while overt attention is hypothesized to serve as an active signaling mechanism in order to communicate with others [44,92,93,94,95]. These dissociations have only just begun to be probed on an experimental level [42,96,97,98,99], with the present study along with Pereira and colleagues’ [45] study providing direct evidence in support of this distinction. Future studies in which covert and overt attention are systematically manipulated and measured are needed to understand the nature of this dissociation.…”
Section: Discussionmentioning
confidence: 99%